2015
DOI: 10.1007/s00256-015-2168-7
|View full text |Cite
|
Sign up to set email alerts
|

An aggressive case of pseudomyogenic haemangioendothelioma of bone with pathological fracture and rapidly progressive pulmonary metastatic disease: case report and review of the literature

Abstract: Pseudomyogenic haemangioendothelioma (PMH) is a rare recently described vascular tumour typically presenting with soft tissue disease in distal extremities of young adults. Multi-focal and multi-layered involvement is commonly recognised. The majority of cases described so far have shown an indolent clinical course and distant metastatic spread is rare. We report a case of PMH in an 82-year-old male diagnosed following a pathological fracture of the distal tibia. Further bone lesions were identified in the fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Approximately one tenth of patients developed metastatic disease, including lung, regional lymph nodes, groin, subpleural region, ribs, and vertebrae [2, 11, 13, 2529]. Few reports demonstrated that a PMHE could have a rapid progression and aggressive behavior [16, 30]. To date, only one case with numerous lytic bone lesions showed a spontaneous regression of the disease with PET/CT [27].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one tenth of patients developed metastatic disease, including lung, regional lymph nodes, groin, subpleural region, ribs, and vertebrae [2, 11, 13, 2529]. Few reports demonstrated that a PMHE could have a rapid progression and aggressive behavior [16, 30]. To date, only one case with numerous lytic bone lesions showed a spontaneous regression of the disease with PET/CT [27].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management is therefore the mainstay of treatment, often in the form of complete but narrow excision or curettage of bone lesions, avoiding large disfiguring surgeries. Although the majority of PHEs pursue a relatively indolent clinical course, several cases of PHE with aggressive clinical behaviour resulting in distant metastasis and death have been reported …”
Section: Newly Described Cutaneous Mesenchymal Neoplasmsmentioning
confidence: 99%
“…Although the majority of PHEs pursue a relatively indolent clinical course, several cases of PHE with aggressive clinical behaviour resulting in distant metastasis and death have been reported. 1,2,6,7 Microscopically, tumours have infiltrative edges and are composed of sheets and loose fascicles of spindled cells with abundant brightly eosinophilic cytoplasm, vesicular nuclei, and small nucleoli ( Figure 1). Tumour cells are cytologically relatively bland, showing only mild atypia and low mitotic activity.…”
Section: Newly Described Cutaneous Mesenchymal Neoplasms P S E U D O mentioning
confidence: 99%
“…Its occurrence in bone is a rare event. To the best of our knowledge, only 27 cases of primary PMHE of bone have been reported so far 4‐17 (Table 1). Few of those reported cases were found to harbor the balanced translocation t(7;19)(q22;q13) producing fusion between SERPINE1 and FOSB genes, 10,12 and only one case was found to carry WWTR1‐FOSB fusion gene 17 .…”
Section: Introductionmentioning
confidence: 99%